Psychoanalysis in a new light. - Karlsson, Gunnar (Cambridge : Cambridge university press, 2010)
1. Phenomenology and psychoanalysis## 2. The life-world as the ground for sciences## 3. A critical examination of neuropsychoanalysis## 4. The conceptualisation of the psychical in psychoanalysis## 5. The libido as the core of the unconscious## 6. The grounding of libido in the life-world experience## 7. Beyond the pleasure principle: the affirmation of existence## 8. The question of truth claims in psychoanalysis## Concluding remarks.
boek